2013
DOI: 10.11604/pamj.2013.15.50.2328
|View full text |Cite
|
Sign up to set email alerts
|

HIV self-testing practices among Health Care Workers: feasibility and options for accelerating HIV testing services in Ethiopia

Abstract: IntroductionHIV is still an enormous global burden and it is also causing loss of huge health care workers (HCWs) on the already limited human resource capacity in health care services in Sub-Saharan Africa. Variety of methods of accelerating HIV testing is required to increase the rate of HIV testing and expand treatment services. Therefore, this study was aimed to find out the prevalence, feasibility and options of HIV self-testing practices in Ethiopia.MethodsA cross-sectional study design triangulated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 14 publications
3
44
1
2
Order By: Relevance
“…However, these studies do provide general insights on HIV testing tendencies among HCWs. In a study of HIVST among HCWs in Ethiopia, it was reported that a higher proportion of nurses than doctors self-tested for HIV, but there was no difference by gender in the proportion of HCWs who reported self-testing [9]. Thus, there is limited information on factors associated with uptake of HIVST among HCWs, and our study has provided some insight on the characteristics of HCWs who find HIVST acceptable.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, these studies do provide general insights on HIV testing tendencies among HCWs. In a study of HIVST among HCWs in Ethiopia, it was reported that a higher proportion of nurses than doctors self-tested for HIV, but there was no difference by gender in the proportion of HCWs who reported self-testing [9]. Thus, there is limited information on factors associated with uptake of HIVST among HCWs, and our study has provided some insight on the characteristics of HCWs who find HIVST acceptable.…”
Section: Discussionmentioning
confidence: 83%
“…In Ethiopia, a study among HCWs showed that 70 % of those who had ever had an HIV test had also self-tested [9], the main reason being the need for privacy. Thus, a well-implemented HIVST program could be an effective way for increasing uptake of HIV testing with increased privacy, and increasing entry into HIV prevention, care and treatment services, such as early ARVs and access to PEP.…”
Section: Introductionmentioning
confidence: 99%
“…While several studies have documented the high acceptance of HIVST among populations [16,[38][39][40] and its convenience [41,42], this, to our knowledge, is the first systematic review and meta-synthesis to assess men's perspectives on HIVST in SSA. While education is key to changing men's perspectives and improving HIV knowledge, this study further revealed that HIV self-testing is critical to addressing issues of confidentiality and convenience [9,16,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…The self-testing approach offers distinct advantages. By giving people the opportunity to test discreetly and conveniently, self-testing may increase the uptake of testing among people not reached by other existing testing services many whom are first-time testers [204][205][206][207]. The experience with hepatitis self-testing is currently very limited, but it represents a potentially important approach to expand access to hepatitis testing in the future.…”
Section: Self-testingmentioning
confidence: 99%